TRADISI BERTUTUR, BUDAYA BER-SMS, DAN SENTUHAN CITARASA SASTRA - Saputra, Heru S.P. (ATAVISME, 2008)
This article discusses the significance between short message service (SMS) popularity in society and oral tradition. The study shows that the using of SMS. or in a broader sense the practice in using information technology, is a cultural process phenomenon which is passing through oral tradition, chirographic culture, typographic. and electronic phase. The processes implies two cultural expression patterns. namely orality and literacy. It indicates that cultural dynamics always sustaining link between the newer and older elements. However, the orality formula still becomes a frame and also a dominant element behind the popularity of literacy culture.